Learning Management System - et. al., S. Arisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is considered as the shaping tool of people. In a developing country like India, education is very important to provide students with practical knowledge and experience. However, during tough situations like that of the pandemic will make in-class education really impossible. There comes the use of online platforms. The systems that are used for the learning of students and for the communication of teachers in a virtual environment are called Learning Management Systems (LMS). The LMS allows students and teachers to obtain quality education at low cost even without coming in real. These LMS were really helpful to cut the overall time wasted on factors like transportation, in between teacher shifting, and much more. Learning Management Systems are created with various factors in mind, which can change according to the needs of various institutions. In this paper, the approach to design a LMS is based on the common needs that any institution would require.